Mobile Flight and Hotel Booking Application: A Heuristic and UX Test - Hussain, Azham; Fitria, Rahma (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The purpose of this study is to present the usability evaluation of the mobile flight and hotel booking application. Currently, mobile applications have offered the easiness to users in order to book flight and hotel. Unfortunately, there is a lack of study on usability that focuses on mobile booking application, while many people start to do all the transactions on their mobile phone. This study will conduct two combined usability evaluation methods which are heuristic and UX test. Ticket.com will be evaluated as it is a critical application that can represent the study of this usability testing. Those selected usability evaluation methods are to evaluate mobile application based on usability experts and end users to get feedbacks and propose solutions and recommendations to improve the application. Observation and questionnaire will be used to measure the metric of effectiveness, efficiency and satisfaction. The heuristic is conducted by three usability experts. Whereas, the UX test participants are ten persons that will be randomly selected either from novice users or the one who experience purchasing flight ticket and hotel reservation on mobile. The result of the study revealed that the application is not easy-to-use and inconsistent as it has been proven by usability score of this application is 66% or below average. It is expected that this study can be adopted by developers and usability practitioners to deliver a user-friendly mobile application that leads to high customer satisfaction.